Kekuatan Islam dan pergulatan kekuasaan di Indonesia : sebelum dan sesudah runtuhnya rezim Soeharto - Aminudin, 1970-; Kamdani (Yogyakarta : Pustaka Pelajar, 1999)
Islamic political dynamics in Indonesia during the Soeharto government
Revision of the author's thesis
Includes bibliographical references (p. 376-384) and index
Keywords: Islam and politics -- Indonesia; Indonesia -- Politics and government -- 1966-1998